Diarrhea and associated factors among under-five children in open defecation free and open defecation rural households of Degem district, Oromia, Ethiopia - Dereje, Demelash; Hailu, Dejene; Debela, Sisay Abebe; Yazew, Tamiru; Tolesa, Fikadu; Abebe, Bogalu (Frontiers in Public Health, 2024)
IntroductionDiarrheal diseases are the top cause of preventable death, particularly among children under the age of five in developing countries like Ethiopia. Despite the national level of latrine coverage being 61%, diarrhea is responsible for the deaths of half a million children under 5 years annually. Therefore, this study aimed to assess diarrhea and its associated factors among children in open defecation free (ODF) and open defecation (OD) households of Degem district, Oromia, Ethiopia.MethodsA comparative cross-sectional study was conducted within the community, involving 398 participants (200 from open defecation free [ODF] and 198 from open defecation [ODF] households). The selection of study participants from OD and ODF households was done using a multistage sampling approach. Data input was carried out using Epi Data 3.1, while data analysis would be performed using Statistical Package for Social Sciences (SPSS) version 26 software, employing appropriate testing methods. Statistical significance and the strength of relationships were assessed using odds ratios with a 95% confidence interval.ResultsThe prevalence of diarrhea among children in open defecation free and open defecation households was 26 and 38%, respectively. Factors such as children who were not vaccinated for rotavirus, mothers or caregivers did not have diarrhea, mothers or caregivers did not wash their hands at critical times, and individuals with poor latrine utilization were significantly associated with diarrhea among children in ODF households. On the other hand, children who were not vaccinated for rotavirus, not received vitamin A supplementation, mothers or caregivers did not wash their hands at critical times, children lacking access to latrines and children whose their families practice open field solid waste disposal were significantly associated with diarrhea among children in open defecation free households.ConclusionThe study results indicated that the prevalence of diarrhea among children under five in open defecation areas was notably higher compared to those residing in open defecation free areas. Consequently, it is imperative for all responsible bodies to focus on evidence-based strategies to combat childhood diarrhea and to ensure child health status.